The Inheritance and Gift Tax in Germany - Reform Potentials for Tax Revenue, Efficiency and Distribution - Martin Beznoska; Tobias Hentze; Maximilian Stockhausen (ZBW - Leibniz Information Centre for Economics, 2020)
The inheritance tax is often seen as an effective tool to reduce wealth inequality, to raise public budgets if needed, and to increase incentives to work by lowering the tax burden on labour, which is especially high in Germany according to the OECD. The purpose of this paper is therefore to shed light on the question whether the inheritance tax is a promising tool for fighting wealth inequality without having distorting effects for the economy. For this purpose, the distributional effects of inheritances on the wealth distribution are evaluated for Germany first and are set into comparison with Austria and France using data from the Household Finance and Consumption Survey (HFCS). A change in the German inheritance tax law in 2009 is further used in a difference-in-difference analysis to identify the behavioural effects of the inheritance tax change on the volume of bequests, which are large and robust for different specifications. Second, the insight from part one is applied to design an inheritance tax reform for Germany. The potential tax revenue of the reform can be estimated by using the data from the inheritance and gift tax statistics for Germany. A revenue shift from income to inheritance tax could be used to increase work incentives by cutting the marginal tax rates for the working population. However, it turns out that taxing inheritances is accompanied by significant behavioural responses of donors via tax planning. Furthermore, the introduction of a flat tax model with a broad tax base would not generate large enough additional revenue to foster relevant employment effects.
Keywords: D31; H20; 330; Inheritance taxation; wealth distribution; redistribution; inequality; labour supply